Design and Development of a Novel Nano-hybrid Dental Composite: Antibacterial Silica Nanocomposite for Dental Use - Nida Asif; Ma Kun; Jahanzeb Sheikh; Eden Haseeb; Rabia Aziz; Ali Dad Chandio; Rashid Khan; Tan Tian Swee; Madeeha Sadia; Syafiqah Saidin (Penerbit Universiti Kebangsaan Malaysia, 2025)
Resin based dental composites is one of the promising dental materials that serves as an alternative to metal and amalgam restorations, as they resemble natural tooth and widely used in restorative dental treatments such as tooth decay and oral lesions. Despite several ongoing researches and innovations, the primary challenges associated with composite restorations are their limited durability, sensitivity, shrinkage and leakage. This research aimed to address these challenges and develop an innovative dental composite resulting in a minimal discomfort to the patient and improve long term therapeutic effi cacy. To overcome these challenges silica Nano- particles, with antibacterial agent was incorporated. Nano- particles of silica acted as filler, which was extracted from a bio-waste (rice husk). The addition of anti-microbial agents helped to minimize leakage due to shrinkage as these materials have small particle size, off ering a wide range of biological, chemical and mechanical properties. This was followed by characterization techniques which includes; SEM, XRD, FTIR and particle characterization that were evaluated and compared. The peaks of Silicon dioxide in XRD was recorded at 21.67, 38.38 and 44.68. Extracted silica particle size 47. 66 μm was further reduced to Nano size with an average size of 200 nm. FTIR spectrum showed the relative transmittance at 1000- 1090 cm-1. The results met the standard measures and was much cheaper than currently used in dental industry. In future, comparative analysis testing including compressive or tensile strength and anti- bacterial testing can be performed that may further prove its potential and can be followed by clinical trials also.